The Importance of Village Apparatus Performance Improvement for Quality Public Services - Sari, Mira Permata; Singgih, Rahadi Pratomo (Jurnal Ilmiah Global Education, 2024)
Village apparatus are public service staff who have duties and responsibilities for services to the community and assist the village head in carrying out his duties to provide services to the community expectations. Therefore, village apparatus is required to have commitment, ability, skills, and feelings of sincere concern and require a high sense of empathy in carrying out their duties to serve the community. The hope is that the community will feel comfortable and satisfied with receiving services from village staff in resolving all administrative problems. However, this is not the case with what happens in the field. There are still many complaints from the public regarding the services provided by the apparatus at the village office. This research is aimed at answering the question of how public services are implemented in village offices in 5 provinces in Indonesia, namely West Java, Data collection was carried out using documentation and semi-structured interviews with community members and staff at the village office. The results of the research show that the indicators of service quality have not been implemented by staff in village offices in Indonesia. Apart from that, the quality of service of staff must be improved through training programs.